2019
DOI: 10.1111/1748-5967.12392
|View full text |Cite
|
Sign up to set email alerts
|

Influence of land consolidation on aquatic invertebrate communities and their distribution patterns in Korean rice fields

Abstract: Rice fields, the major cropland in South Korea, provide an important wetland habitat for a diverse wildlife and contribute to biodiversity conservation. On the other hand, land consolidation conducted to increase agricultural production since the 1960s on a nationwide scale in South Korea has frequently been suggested to be one of the factors in the decline of biodiversity in agricultural ecosystems. Negative effects of habitat manipulation such as land consolidation would have influenced paddy field biodivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
2
2
0
Order By: Relevance
“…The lower richness and evenness of wild pollinator communities in landscapes with consolidated farmland as compared to traditional farmland is in line with our first hypothesis, and aligns with findings for aquatic invertebrate in Korean rice systems (Nam et al, 2019) and plant communities in Japan (Osawa et al, 2016). The relatively low pollinator diversity in consolidated fields might be associated with the deterioration of the fine-scale network of vegetation on the edges between fields, as the management of the oilseed rape crops was similar, i.e., based on farmer's own practice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The lower richness and evenness of wild pollinator communities in landscapes with consolidated farmland as compared to traditional farmland is in line with our first hypothesis, and aligns with findings for aquatic invertebrate in Korean rice systems (Nam et al, 2019) and plant communities in Japan (Osawa et al, 2016). The relatively low pollinator diversity in consolidated fields might be associated with the deterioration of the fine-scale network of vegetation on the edges between fields, as the management of the oilseed rape crops was similar, i.e., based on farmer's own practice.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in consolidation, finely interwoven semi-natural habitats in farmland is lost. While negative impacts of land consolidation have been reported on aquatic invertebrates (Nam et al, 2019) and wild plants (Osawa et al, 2016), the effect of land consolidation on wild pollinators has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our hypothesis #1, we found that the abundance and richness of natural enemies were lower in rice fields in consolidated farmlands than in traditional farmlands. This finding aligns with previous studies reporting negative effects of land consolidation on pollinator communities (Shi et al., 2021), aquatic arthropods (Nam et al., 2019), and birds (Denac & Kmecl, 2021). The main reason might be that land consolidation eliminated natural vegetation cover on the field margins, while these field margins can provide nesting habitat and food sources for natural enemies (Marshall & Moonen, 2002; Vickery et al., 2009).…”
Section: Discussionsupporting
confidence: 92%
“…During the consolidation process, the removal of linear habitats may result in biodiversity loss (Li et al., 2019; Shi et al., 2021; Zhang et al., 2012). Compared to traditional lands, consolidated farmlands have a lower diversity of pollinators, probably due to the removal of flowering plants in field margins (Shi et al., 2021), and a lower diversity of aquatic arthropods due to the reduction of small irrigation ponds and ditches (Nam et al., 2019). Therefore, while farmland consolidation may increase agricultural efficiency (General Administration of Quality Supervision, 2014; Ministry of Natural Resources of the People's Republic of China, 2021), the potential impacts on biodiversity need to be evaluated (Zou, 2024).…”
Section: Introductionmentioning
confidence: 99%